Efektivitas Perlindungan HKI bagi UMKM di Indonesia dan Perbandingannya dengan Negara Lain - Angelica Jovanka Sukarsaatmadja; Gunardi Lie (PT. Hasba Edukasi Mandiri, 2025)
Intellectual Property Rights (IPR) are legal rights that protect the creations, inventions, and creativity that possess economic value. In the context of business law, IPR protection, particularly trademark protection is crucial for Micro, Small, and Medium Enterprises (MSMEs) as it safeguards their product identity and competitiveness. Indonesia has established a strong legal foundation for IPR protection through Law No. 20 of 2016 on Trademarks and Geographical Indications, Law No. 28 of 2014 on Copyright, Law No. 13 of 2016 on Patents, and Law No. 30 of 2000 on Trade Secrets, which have been harmonized with international standards under the TRIPS Agreement (Trade-Related Aspects of Intellectual Property Rights). However, the effectiveness of IPR protection for MSMEs in Indonesia remains suboptimal due to the application of the first to file principle, which often creates inequality for small businesses that face obstacles in trademark registration. The MS Glow vs PS Glow case exemplifies the weakness of IPR protection implementation in Indonesia. In this case, the court ruled in favor of the party that registered the trademark first, without considering the social and economic aspects of the business that had already gained a stronger market reputation. This outcome demonstrates that Indonesia’s IPR protection system still emphasizes formal legal certainty rather than substantive justice. Conversely, countries such as Japan and South Korea have successfully implemented more effective IPR protection systems through government support in the form of registration subsidies, free legal assistance, and efficient dispute resolution mechanisms via institutions such as the Japan Patent Office (JPO) and the Korean Intellectual Property Office (KIPO). This article employs a normative legal research method with a comparative approach to examine the effectiveness of IPR protection for MSMEs in Indonesia and compare it with the systems in Japan and South Korea. The findings reveal that, although Indonesia has established a comprehensive legal framework, its implementation remains ineffective due to limited legal literacy, high costs, and insufficient access to legal assistance for MSMEs. Therefore, it is necessary to strengthen institutional capacity, enhance legal education, provide registration subsidies, and develop non-litigation dispute resolution mechanisms to ensure fair and effective IPR protection. A robust IPR protection system will play a vital role in encouraging innovation, enhancing the competitiveness of MSMEs, and strengthening a creativity-based national economy.